Air-borne propagules of Colletotrichum falcatum and their role in the epidemiology of sugarcane red rot - SUNITA LAL, R.P. SINGH and (Indian Phytopathology, 2002)
The role of airborne propagules of C. falcatum [Glomerella tucumanensis] in red rot disease of sugarcane in Uttar Pradesh, India, was investigated. Sugarcane cultivars Co 312 and Co 997 were inoculated with a virulent G. tucumanensis isolate in Sep.In Dec. and Jan. airborne particles were trapped using glass slides coated in vaseline at varying distances from the plants. Slides were replaced after 8 h and examination under a microscope revealed the presence of broken setae, dried acervuli, hyphalpieces and appressoria. At harvest, healthy canes growing near diseased canes had localised nodal infection (12% of Co 312 and 6% of Co 997). It is concluded that airborne propagules may have a significant role in the epidemiology of sugarcane red rot.